Untersuchung der linearen Stabilität derTaylor-Couette-Strömung mittelsPolynomentwicklung höherer Ordnung - Patrick Diffo (2011)
High Intensity Discharge (HID) lamps are light generating devices made of a ceramics or quartz arc tube also called burner which confines a gas mixture, usually mercury with some additives, and two electrodes. The imposition of current between these electrodes leads to the ionization of the gas, bringing it to temperatures between 5000 and 6000 K in a light-emitting region named the arc (see Figure 1 left). HID lamps find common applications in expansive outdoor spaces like streets, roadways, parking lots, stadiums, etc. The indoor applications, such as shop lighting, are on their side optimally operated at an alternate current frequency of around 300 kHz which can lead to an unstable plasma arc (lamp flicker in Figure 1 right) and even to an early lamp failure (paper Baumann). Acoustic resonance has been presumed for some years now to be the effect behind this arc instability [15]. For an accurate description of the effect’s onset we refer to [14] and references therein. Since a new approach is undertaken, where an overlapping of the acoustic resonance with the temperature driven gas hydrodynamic instability is presumed.